The Effect of Studios on Learning in Design Education - Düzenli, Tuğba; Alpak, Elif Merve; Çiğdem, Abdullah; Tarakçı Eren, Emine (Journal of History Culture and Art Research, 2018)
The present study that aimed to determine the effects of the project classes conducted in the design studio on students was scrutinized specifically on the studio work conducted within the context of Environmental Design Project Course studio practice in Karadeniz Technical University Landscape Architecture Department. The study was a studio practice. In the first phase of the study, the content and practice of the studio course was examined. In the next phase, a survey was conducted with 174 students to investigate the effects of the fact that the courses were conducted in the studio environment on design students. The survey aimed to inquire the effects of the studio on the students’ creativity, development and learning of design skills. The satisfaction of the students in this course and their views about the use of the process in their future professional life was studied. Survey questions were asked to freshmen, sophomore, junior and senior students and the differences between these classes were determined. The questions were assessed using a 5-point Likert attitude scale. Conducted statistical analyses (SPSS 23.0) demonstrated that students considered the studios as environments that improve their creativity the most, students at all levels were satisfied with the studios, but that their satisfaction increased with their seniority, and they wanted to utilize this process in their professional lives and this desire was most prevalent among senior students. Correlation analysis findings demonstrated that satisfaction with the process was mostly related to the learning process. The present study findings demonstrated that design studios were instruction environments that provide students with design skills, improve their creativity and provide them practice opportunities. Study findings also revealed that the students were satisfied with design courses instructed in the studio and desired to experience the same process in their professional lives as well.